IMPLEMENTASI PRAKTIK GREEN HUMAN RESOURCES MANAGEMENT: (Studi Kasus pada Perusahaan Pertambangan) - Siburian, Nia Adonia; Sugiarto*, Agus (JURISMA : Jurnal Riset Bisnis & Manajemen, 2022)
The purpose of this study is to explore how the process of implementing the Green HRM concept is, what are the challenges and obstacles as well as the impact of implementing the Green HRM concept. Informants in this study are site managers and production managers. The research method is a case study qualitative approach, data collection is carried out by in-depth interviews and observations of bauxite mining companies in West Kalimantan. The data analysis of this research used interactive data analysis. The results show that the company has not perfectly and explicitly implemented Green HRM. However, the company has made efforts to build green employee behavior in the aspects of recruitment and selection, employee training and development, compensation and benefits, organizational culture, and performance management. Some of the benefits obtained in implementing Green HRM are that employees live healthier, have a good reputation for the company, are skilled and committed employees, reduce negative impacts on the environment, reduce waste and recycle waste thereby reducing production costs. Keywords : Human Resource, Green Human Resource, Sustainability, Management, Mining Company